The Parkin'Play study: protocol of a phase II randomized controlled trial to assess the effects of a health game on cognition in Parkinson's disease. Issue 1 (December 2016) - van de Weijer, Sjors; Duits, Annelien; Bloem, Bastiaan; Kessels, Roy; Jansen, Jacobus; Köhler, Sebastian; Tissingh, Gerrit; Kuijf, Mark
Abstract Background In Parkinson's disease (PD), cognitive impairment is an important non-motor symptom heralding the development of dementia. Effective treatments to slow down the rate of cognitive decline in PD patients with mild cognitive impairment are lacking. Here, we describe the design of the Parkin'Play study, which assesses the effects of a cognitive health game intervention on cognition in PD. Methods/Design This study is a multicentre, phase-II, open-randomized clinical trial that aims to recruit 222 PD patients with mild cognitive impairment. Eligible patients have PD, Hoehn & Yahr stages I–III, are aged between 40 and 75 years, and have cognitive impairment but no dementia. The intervention group (n = 111) will be trained using a web-based health game targeting multiple cognitive domains. The control group (n = 111) will be placed on a waiting list. In order to increase compliance the health game adapts to the subjects' performance, is enjoyable, and can be played at home. From each group, 20 patients will undergo fMRI to test for potential functional brain changes underlying treatment. The primary outcome after 12 weeks of training is cognitive function, as assessed by a standard neuropsychological assessment battery and an online cognitive assessment. The neuropsychological assessment battery covers the following domains: executive function, memory, visual perception, visuoconstruction and language. A compound score for overall cognitive function will be calculated as the mean score of all test Z-scores based on the distribution of scores for both groups taken together. Secondary outcomes at follow-up visits up to 24 weeks include various motor and non-motor symptoms, compliance, and biological endpoints (fMRI). Discussion This study aims at evaluating whether a cognitive intervention among PD patients leads to an increased cognitive performance on targeted domains. Strengths of this study are a unique web-based health game intervention, the large sample size, a control group without intervention and innovations designed to increase compliance. Trial registration NTR5637 on 7-jan-2016